The Role of Vitamin D in Stunting Prevention: A Literature Review - Mardiah, Wiwi; Setiabudiawan, Budi; Mediani, Henny Suzana (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Nutritional problems in infants under the age of two can inhibit growth and development. This has a negative impact on their subsequent life, increasing the risk of stunting. Vitamins are essential micronutrients in the body’s metabolic processes and they have a multi-complex role. One of the micronutrients that affect stunting are vitamin D. It plays an important role in stunting prevention. Stunting countermeasures are carried out by fulfilling the need of adequate nutrition where both macronutrients and micronutrients are needed to avoid the risk of stunting. AIM: The aim of this literature review was to analyze the role of vitamin D in preventing stunting. METHODS: The articles were collected through the Google Scholar, PubMed, Proquest, and Ebsco databases using the keywords Vitamin D and Stunting, consisting of both quantitative and qualitative studies. The articles used were only articles with a full text available that were written in English and Indonesian published from 2015 to 2019. Fifteen articles were found that met the criteria. RESULTS: The literature review results indicate that vitamin D plays an important role in the metabolism of bone formation and growth. It also has the role of increasing the level of immunity in children. Both roles contribute to stunting prevention. Vitamin D is key in regulating the immune function during pregnancy regarding the fetus-mother interaction, representing an important target. Among its non-classical actions include the emphasis of strong immunomodulators, including the induction of antibacterial responses and the modulation of T-lymphocytes to suppress inflammation and increase tolerogenesis. Vitamin D plays an important role in the innate immune function in the decidua by promoting the infection response while simultaneously preventing the excessive elaboration of immune inflammation. The research to date has focused on the potential role of vitamin D in preventing infectious diseases such as tuberculosis, as well as possibly suppressing autoimmune diseases. CONCLUSION: Vitamin D can also affect the immune function in a manner that is not immediately related to the primary innate response. Stunting can be prevented early on through the adequate intake of macro and micronutrient nutrients. The need for micronutrients is especially important, inclusive of vitamin D as an important element in bone metabolism. It also increases the body’s defenses so as to prevent infectious diseases in children.